Checklist of the Decapods (Crustacea) from the Fernando de Noronha Archipelago, Brazil - de Lourdes Alves, Maria; Ramos-Porto, Marilena; Viana, Girlene Fábia Segundo (Zootaxa, 2008)
This work presents a list of crustacean decapods species collected around Fernando de Noronha Archipelago, between November 1991 and August 1993, and also January 2000. This report lists others species reported in the area from records in the literature as well as those collected during the Almirante Saldanha Expedition. A total of 133 species are recorded belonging to 45 families from the Suborder Dendrobranchiata and the Infraorders Stenopodidea, Caridea, Astacidea, Thalassinidea, Palinura, Anomura and Brachyura of the Suborder Pleocyemata.